Necessità di un nuovo approccio al mercato delle PI. Il contributo della letteratura di marketing - Ferrero, Giancarlo; Fortezza, Fulvio; Savelli, Elisabetta (Piccola Impresa / Small Business, 2012)
In the current scenario, SMEs are facing a strong decline, both numerically and in terms of economic/financial difficulties that companies active have to beard. Expansionary economic policies are not enough to re-establish the SMEs’ competitiveness. Structural changes are needed within SMEs, based on the transition from cost-saving strategies to differentiation strategies aimed at increasing the value created and the company’s ability to do it correctly perceive to customers. A deeper culture of marketing among SMEs seems to be necessary to this end, based on methods and practices consistent with the small size of these enterprises. The paper proposes a review of recent studies on small business marketing and discusses the "pre-conditions" to be created in order to develop a marketing-oriented approach among SMEs.